The Legionella pneumophila Chaperonin – An Unusual Multifunctional Protein in Unusual Locations - Garduno, Rafael A.; Chong, Audrey; Nasrallah, Gheyath K.; Allan, David S. (Frontiers in Microbiology, 2011)
The L. pneumophila chaperonin, HtpB, was discovered as a highly immunogenic antigen, only a few years after the identification of L. pneumophila as the causative agent of Legionnaires’ disease. As its counterparts in other bacterial pathogens, HtpB did not initially receive further attention, particularly because research was focused on a few model chaperonins that were used to demonstrate that chaperonins are essential stress proteins, present in all cellular forms of life and involved in helping other proteins to fold. However, chaperonins have recently attracted increasing interest, particularly after several reports confirmed their multifunctional nature and the presence of multiple chaperonin genes in numerous bacterial species. It is now accepted that bacterial chaperonins are capable of playing a variety of protein folding-independent roles. HtpB is clearly a multifunctional chaperonin that according to its location in the bacterial cell, or in the L. pneumophila-infected cell, plays different roles. HtpB exposed on the bacterial cell surface can act as an invasion factor for non-phagocytic cells, whereas the HtpB released in the host cell can act as an effector capable of altering organelle trafficking, the organization of actin microfilaments and cell signaling pathways. The road to discover the multifunctional nature of HtpB has been exciting and here we provide a historical perspective of the key findings linked to such discovery, as well as a summary of the experimental work (old and new) performed in our laboratory. Our current understanding has led us to propose that HtpB is an ancient protein that L. pneumophila uses as a key molecular tool important to the intracellular establishment of this fascinating pathogen.